2017
DOI: 10.1038/s41598-017-05338-5
|View full text |Cite
|
Sign up to set email alerts
|

Ammonium chloride alters neuronal excitability and synaptic vesicle release

Abstract: Genetically encoded pH-sensors are widely used in studying cell membrane trafficking and membrane protein turnover because they render exo-/endocytosis-associated pH changes to fluorescent signals. For imaging and analysis purposes, high concentration ammonium chloride is routinely used to alkalize intracellular membrane compartments under the assumption that it does not cause long-term effects on cellular processes being studied like neurotransmission. However, pathological studies about hyperammonemia have s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 69 publications
0
22
0
Order By: Relevance
“…Importantly, we do not recommend using NH 4 Cl for increasing staining specificity because of the possible disruptive effects on the cell physiology. 23 …”
Section: Resultsmentioning
confidence: 99%
“…Importantly, we do not recommend using NH 4 Cl for increasing staining specificity because of the possible disruptive effects on the cell physiology. 23 …”
Section: Resultsmentioning
confidence: 99%
“…Hyperammonemia is closely associated with neuronal cell death, the disruption of neuronal morphology, synaptic vesicle release, and long-term synaptic change [ 7 , 31 ]. Patients with minimal hepatic encephalopathy have shown impaired learning and memory, accompanied by changes in the hippocampal structure and function [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative Medicine and Cellular Longevity cells exposed to NH 4 Cl metabolize this molecule into ammonia [31]. The SH-SY5Y cells were differentiated into neurons, treated with siRNA against each lncRNA as well as NH 4 Cl, and then used to investigate the role of these lncRNAs during hyperammonemia-induced apoptosis (see Materials and Methods).…”
Section: Selection Of Lncrnas Involved In the Pathogenesis Ofmentioning
confidence: 99%
“…Clearly, both pH manipulations have a possible impact on synaptic vesicle behavior. Notably, our recent paper demonstrated that even a moderate concentration of NH 4 Cl ( i.e ., 5 mM) can change synaptic vesicle release and retrieval over an extended period of time (Lazarenko et al ., 2017). …”
Section: Introductionmentioning
confidence: 99%
“…The methods were adapted from (Lazarenko et al ., 2017). Techniques were also adapted from all of the references cited.…”
mentioning
confidence: 99%